2015
DOI: 10.1002/hyp.10708
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of grid precipitation data for Brazil: application in river discharge modelling of the Tocantins catchment

Abstract: Abstract:Here, we compared grid precipitation data -Climate Forecast System Reanalysis (CFSR) and WATCH Forcing Data methodology applied to ERA-Interim (WFDEI) data -with Brazilian Weather Bureau (INMET) and Brazilian Water Agency (ANA) rain gauge data (n = 2027) for the period 1980-2010 in order to evaluate which grid data set better represents precipitation, and is thus more suitable for hydrological modelling of Brazilian water resources. We found that WFDEI outperformed CFSR according to three statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 34 publications
4
33
0
11
Order By: Relevance
“…The results found here clearly show that the original NCEP-CFSR precipitation is not suitable to apply for streamflow simulations in Malaysia, which is in agreement with the findings of Monteiro et al [27], Roth and Lemann [64] and Bressiani et al [87] for other tropical or sub-tropical conditions. However, the results found here conflict with the findings of Jajarmizadeh et al [88], who report successful SWAT streamflow simulation results using the NCEP-CFSR data for the Roodan watershed that is located in southern Iran.…”
Section: Discussionsupporting
confidence: 90%
“…The results found here clearly show that the original NCEP-CFSR precipitation is not suitable to apply for streamflow simulations in Malaysia, which is in agreement with the findings of Monteiro et al [27], Roth and Lemann [64] and Bressiani et al [87] for other tropical or sub-tropical conditions. However, the results found here conflict with the findings of Jajarmizadeh et al [88], who report successful SWAT streamflow simulation results using the NCEP-CFSR data for the Roodan watershed that is located in southern Iran.…”
Section: Discussionsupporting
confidence: 90%
“…Dile and Srinivasan [15] highlighted the benefit of using the CFSR product in sparsely-monitored regions, where CFSR and conventional databases led to minor differences, except for one watershed for which CFSR gave much higher average annual rainfall. Monteiro, et al [16] demonstrated the superiority of one ERA-derived product (WFDEI-WATCH Forcing Data ERA Interim [17]) over CFSR. Finally, in a comparison of several weather input datasets, de Almeida Bressiani, et al [18] concluded that the best option for hydrological simulation is the CFSR product used with ground-based climate data.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted initial tests on the available data prior to calibration, then chose the data that appeared to perform the best based on certain model efficiency criteria [16,17]. Others studied the sensitivity of model outputs to precipitation ensembles [18,19], and their effects on water resource components of non-calibrated models [14,15,20]. Although all these schemes are important and necessary, in all of them, the prediction uncertainty was based on only one dataset.…”
Section: Introductionmentioning
confidence: 99%